2021
DOI: 10.1038/s41598-021-98553-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of continuous positive airway pressure therapy on blood pressure in patients with obstructive sleep apnea

Abstract: Obstructive sleep apnea (OSA) is a common cause of hypertension. Previous studies have demonstrated beneficial short-term effects of continuous positive airway pressure (CPAP) therapy on blood pressure. However, long-term antihypertensive effects of CPAP have not been properly verified. This study examined the longitudinal effect of CPAP therapy adherence on blood pressure among OSA patients. All patients diagnosed with OSA and undergoing subsequent CPAP therapy at a Kanagawa-area sleep clinic were clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…PAP regulation of the neurovegetative and hormonal determinants of HTN explains its beneficial effect on BP levels and the circadian pattern, especially in patients with resistant hypertension [ 59 , 60 ]. However, a recent report also noted improvement in BP values in normotensive patients, suggesting that PAP adherence could modulate the baroreflex threshold [ 61 ]. Furthermore, PAP therapy seems to have a more robust effect on the diastolic BP value [ 61 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAP regulation of the neurovegetative and hormonal determinants of HTN explains its beneficial effect on BP levels and the circadian pattern, especially in patients with resistant hypertension [ 59 , 60 ]. However, a recent report also noted improvement in BP values in normotensive patients, suggesting that PAP adherence could modulate the baroreflex threshold [ 61 ]. Furthermore, PAP therapy seems to have a more robust effect on the diastolic BP value [ 61 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report also noted improvement in BP values in normotensive patients, suggesting that PAP adherence could modulate the baroreflex threshold [ 61 ]. Furthermore, PAP therapy seems to have a more robust effect on the diastolic BP value [ 61 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight loss and CPAP use were not significantly associated (= 0.02, p = 0.59). Lowered DBP without appreciable weight reduction was linked to long-term, good CPAP therapy adherence [ 21 ]. The most extraordinary sample size was used in a multicenter, RCT by Barbé et al which demonstrated a modest drop in blood pressure.…”
Section: Reviewmentioning
confidence: 99%
“…The gold standard therapy for moderate to severe OSA is overnight continuous positive airway pressure (CPAP) delivered via a nasal or facial mask (8), which prevents pharyngeal collapse. In addition to markedly reducing the number of apnea and hypopnea events during sleep, treatment of OSA with CPAP has been shown to have several beneficial effects, including improvements in sleepiness, cognition and mood, and reductions in blood pressure (9)(10)(11)(12). Treatment with CPAP has also been shown to reduce hospitalization rates and healthcare costs (13), and may also reduce mortality (14).…”
Section: Introductionmentioning
confidence: 99%